Color image encryption via Hénon-zigzag map and chaotic restricted Boltzmann machine over Blockchain. (March 2021) - Feixiang, Zhao; Mingzhe, Liu; Kun, Wang; Hong, Zhang
Highlights: A random number generator, chaotic restricted Boltzmann machine (CRBM) is designed. A color image encryption algorithm using the Hénon-zigzag map and CRBM is proposed. Asymmetric image encryption system with tamper detection capability is designed. Abstract: A color image encryption algorithm using the Hénon-zigzag map and chaotic restricted Boltzmann machine (CRBM) is proposed in this paper. The proposed pseudo-random number generator, chaotic restricted Boltzmann machine (CRBM), can simultaneously generate three pseudo-random number sequences. The algorithm includes the permutation phase and the diffusion phase. In the Hénon-zigzag map-based permutation phase, zigzag map is used to modulate two pseudo-random number sequences generated by Hénon map to obtain two new pseudo-random number sequences. The mixing of these two chaotic maps makes the security of the permutation phase significantly improve. Subsequently the two pseudo-random number sequences are used for row permutation and column permutation, respectively. In the diffusion phase, through multiple iterations of CRBM of the 3 × 3 architecture, three pseudo-random number sequences are generated by the state values of three neurons in the visible layer. Then these three pseudo-random number sequences are used for bitxor operation with the R, G and B components of the scrambled image, respectively. A series of numerical experiments and analyses on encrypted images prove that the proposed algorithm is more secure than state-of-the-art algorithms. Furthermore, based on the combined use of blockchain and the proposed algorithm, a novel image encryption/decryption system is proposed. The system has two features: asymmetric encryption/decryption of images and authoritative verification of the integrity of encrypted images. It may provide a better understanding of blockchain in digital image encryption.